2010
DOI: 10.1016/j.jcis.2010.08.085
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning of catalytic tin nanoparticles by the reverse micelle method for direct deposition of silicon nanowires by a plasma-enhanced chemical vapour technique

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. AbstractThe reverse micelle method was used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Those micelles might restrict the diffusion and growth of Y 3+ ions as well as precursor nanoparticles by Coulombic attraction during the homogeneous precipitation reaction. It has been reported that surfactant micelles reduce the oxygen bridge bonds between nanoparticles, resulting in a reduced agglomeration tendency . Moreover, CTAB micelles that are adsorbed on the precursor particles may reduce the surface free energy of the precursor particles and thus possibly retard the agglomeration in the aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those micelles might restrict the diffusion and growth of Y 3+ ions as well as precursor nanoparticles by Coulombic attraction during the homogeneous precipitation reaction. It has been reported that surfactant micelles reduce the oxygen bridge bonds between nanoparticles, resulting in a reduced agglomeration tendency . Moreover, CTAB micelles that are adsorbed on the precursor particles may reduce the surface free energy of the precursor particles and thus possibly retard the agglomeration in the aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that surfactant micelles reduce the oxygen bridge bonds between nanoparticles, resulting in a reduced agglomeration tendency. 20,21 Moreover, CTAB micelles that are adsorbed on the precursor particles may reduce the surface free energy of the precursor particles and thus possibly retard the agglomeration in the aqueous medium. However, in this study we cannot report about the exact critical micelle concentration effect with respect to the growth of Y(OH)CO 3 nanoparticles which is due to the heterogeneous reaction environment (presence of metal nitrates, urea, intermediates of urea, ammonia, carbonates, and hydroxides).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above knowledge, Sn nanomaterials have huge application prospects in many areas of human life, so the research on the preparation of nano-Sn is getting more and more attention from researchers. Various procedures have been proposed and applied to obtain Sn nanoparticles, such as mechanical alloying technology [10], arc discharge technology [11], metal vapor condensation technology [12], liquid-phase reduction [13], physical vapor deposition (PVD) [14], chemical liquid deposition (CLD) [15], electrochemical method [16], reverse micelle method [17] and so on. For example, Chee et al [18] used stannous octoate as a raw material, sodium borohydride as a reducing agent, and polyvinylpyrrolidone (PVP) as a surfactant to study the effects of reaction temperature, drying temperature, ultrasonic vibration, and centrifugal speed on the size of Sn nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this research is to establish the technique of producing Sn nanoparticles from a bulk Sn material using the in-liquid plasma method. Various processes have been proposed for synthesis of nanoparticles ranging from solution dispersion 1) 2) , the chemical reduction method 3) ~ 5) , the modified polyol process 6) , laser pyrolysis 7) , sonochemical synthesis 8) 9) , the reversed micelle method 10) , electrospraying 11) , to the electrolysis method 12) .…”
Section: Introductionmentioning
confidence: 99%